CD28 Genetic Variants Increase Susceptibility to Diabetic Kidney Disease in Chinese Patients with Type 2 Diabetes: A Cross-Sectional Case Control Study - Yangyang Li; Li Jin; Jing Yan; Hong Zhang; Rong Zhang; Cheng Hu (Mediators of Inflammation)
Few studies have illuminated the genetic role of T cell costimulatory molecule CD28/CD80/CTLA4 variants in diabetic kidney disease (DKD) susceptibility. We aimed to investigate the causal role of genetic polymorphisms in CD28/CD80/CTLA4 with DKD susceptibility in patients with T2DM. A total of 3253 patients with T2DM were recruited for genotyping: including 204 DKD patients and 371 controls in stage 1 and 819 DKD patients and 563 controls in stage 2; besides, 1296 T2DM patients were selected for the analysis of association between loci and DKD-related traits. A subset of 227 T2DM patients (118 patients with DKD and 109 patients without DKD) from the total population above were selected to assess serum soluble CD28 (sCD28) levels. Then, we performed a candidate gene association study to identify single-nucleotide polymorphisms (SNPs) associated with DKD susceptibility and further used those SNPs to perform Mendelian randomization analyses of serum sCD28 level and DKD susceptibility. Under additive genetic models, CD28-rs3116494 (OR=1.29 [95% CI 1.11, 1.51], P=0.0011) and CD80-rs3850890 (OR=1.16 [95% CI 1.02, 1.31], P=0.0283) were associated with DKD susceptibility adjusted for age, gender, body mass index (BMI), duration of diabetes, and HbA1c. CD28-rs3116494 was associated with serum sCD28 level (β=0.26 [95% CI 0.08, 0.44], P=0.0043). The Mendelian randomization analysis showed that CD28-rs3116494 played a causal role in DKD by influencing serum sCD28 levels (β=1.15 [95% CI 0.46, 1.83], P=0.0010). In conclusion, we identified that two novel SNPs, CD28-rs3116494 and CD80-rs3850890, were associated with DKD susceptibility. Using the Mendelian randomization analysis, our study provided evidence for a causal relationship between serum CD28 levels and DKD with T2DM in the Chinese population.